Teknologi Digital dan Kesejahteraan Psikologis Karyawan Generasi Z: Tinjauan Sistematis di Dunia Kerja Modern - Widodo, Nikita Amanda Putri; Chusniyah, Tutut (Flourishing Journal, 2025)
The development of digital technology in the modern workplace presents both efficiency opportunities and challenges for the psychological well-being of Generation Z employees. This study is a systematic review based on PRISMA guidelines and JBI quality assessment of nine relevant articles (2019–2025) that discuss the relationship between work technology and the psychological well-being of Gen Z. The analysis in this study highlights how the use of digital technology in the workplace can trigger psychological stress such as digital stress, technostress, and burnout, which ultimately worsens various aspects of the psychological well-being of Generation Z employees. The findings show that technology (e.g., collaboration platforms, communication applications, and work algorithms) has the potential to increase productivity and flexibility, but also increases technostress, digital fatigue, and the blurring of work-life boundaries that negatively impact most dimensions of Psychological Well-Being (especially autonomy, environmental mastery, positive relations, and purpose in life). This study emphasizes the importance of digital strategies that are not only technically based but also humanistic in designing a healthy and inclusive future work ecosystem for Generation Z. AbstrakPerkembangan teknologi digital dalam dunia kerja modern menghadirkan peluang efisiensi sekaligus tantangan bagi kesejahteraan psikologis karyawan Generasi Z. Kajian ini merupakan tinjauan sistematis berdasarkan pedoman PRISMA dan penilaian kualitas JBI terhadap sembilan artikel relevan (2019–2025) yang membahas hubungan teknologi kerja dengan kesejahteraan psikologis Gen Z. Analisis dalam kajian ini menyoroti bagaimana penggunaan teknologi digital di tempat kerja dapat memicu tekanan psikologis seperti digital stress dan technostress yang pada akhirnya memperburuk berbagai aspek kesejahteraan psikologis karyawan Generasi Z. Temuan menunjukkan bahwa teknologi (mis. platform kolaborasi, aplikasi komunikasi, dan algoritme kerja) berpotensi meningkatkan produktivitas dan fleksibilitas, tetapi juga meningkatkan technostress, kelelahan digital, dan kaburnya batas kerja-hidup yang berdampak negatif pada sebagian besar dimensi psychological well-being (terutama autonomy, environmental mastery, positive relations, serta purpose in life). Studi ini menegaskan pentingnya strategi digital yang tidak hanya berbasis teknis, tetapi juga humanistik, dalam mendesain ekosistem kerja masa depan yang sehat dan inklusif bagi Generasi Z.